2023
DOI: 10.2147/prbm.s421544
|View full text |Cite
|
Sign up to set email alerts
|

Grit and Academic Self-Efficacy as Serial Mediation in the Relationship Between Growth Mindset and Academic Delay of Gratification: A Cross-Sectional Study

Abstract: Purpose With a growth mindset, individuals focus on the process of growth, actively seek challenges, recognise and accept failures, and apply more effort and monitor themselves to overcome difficulties. Doing so translates into excellent academic performance. However, it has not yet been fully clarified how growth mindset affects academic delay of gratification (ADG) and the mechanisms underlying their interactions. In this study, grit and academic self-efficacy were tested as mediating mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 79 publications
3
10
0
Order By: Relevance
“…In addition, in terms of intervention pathways for academic self-efficacy, the main interventions have been formulated in terms of confidence, beliefs, emotions, and attitudes, and it is believed that learning psycho-efficacy training [19] and positive emotions [20] can enhance the academic self-efficacy of students. Educational intervention pathways have mainly been formulated in terms of learning methods, learning behaviors, and so on (e.g., teachers guiding learners to enhance their academic self-efficacy) [21,22]. Furthermore, a student's perception of the classroom environment can enhance their academic self-efficacy [23], and the effectiveness of feedback information influences the improvement of academic self-efficacy [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in terms of intervention pathways for academic self-efficacy, the main interventions have been formulated in terms of confidence, beliefs, emotions, and attitudes, and it is believed that learning psycho-efficacy training [19] and positive emotions [20] can enhance the academic self-efficacy of students. Educational intervention pathways have mainly been formulated in terms of learning methods, learning behaviors, and so on (e.g., teachers guiding learners to enhance their academic self-efficacy) [21,22]. Furthermore, a student's perception of the classroom environment can enhance their academic self-efficacy [23], and the effectiveness of feedback information influences the improvement of academic self-efficacy [24].…”
Section: Introductionmentioning
confidence: 99%
“…The “other” aspects, such as family and school environments ( Goswami, 2012 ; Lampropoulou, 2018 ), parents and their parenting styles ( Li R. et al, 2020 ), learning and academic performance ( Liu and Zhang, 2006 ), as well as the personality and emotional experiences ( Ortiz Alvarado et al, 2019 ), are the main focus of current research on the learning subjective well-being of high school students, with less attention paid to the growth mindset of high school students ( King and Trinidad, 2021 ). Furthermore, drawing from existing research evidence and theories, achievement motivation and grit may serve as potential mediating mechanisms between a growth mindset and learning subjective well-being ( Liu et al, 2021 ; Zhao et al, 2022 ). Therefore, this study aims to explore in detail the impact of a growth mindset on the learning subjective well-being of high school students, while examining the mediating role of achievement motivation and grit.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Social Intuitionist Theory, people use their beliefs to predict and select their own behavior by judging and explaining the objects and phenomena in their environment ( Heider, 1958 ). People who have a growth mindset frequently think that ability develops incrementally, believing that abilities are variable and can be developed ( Dweck, 2006 ; Diao et al, 2020 ; Zhao et al, 2022 ). They will proactively learn to reach their full potential, exhibit bravery in the face of academic difficulties, persevere in the face of setbacks, and choose to put in more effort to achieve their goals ( Zhao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that individuals' implicit thinking is not easily perceived in everyday life, but it has a positive impact on their psychology and behaviour; those who have a growth mindset can recognize their own abilities and are more likely to achieve their goals and appreciate their own significance and value. 65,66 Coping theory suggests that individuals with a high propensity for gratitude are better able to use resources to satisfy their psychological needs, work hard to achieve their goals, believe more strongly in their ability to change their current situation, and easily realize the meaning and value of life when they succeed. 67 Compared with previous studies, this study is innovative because it explored the relationship through a behavioural experimental approach and identified the psychological mechanisms and moderating variables through which growth mindset affects sense of meaning through a cognitive perspective.…”
mentioning
confidence: 99%